PEMBINAAN TEKNOLOGI PETANI DALAM PENGEMBANGAN ANEKA PRODUK TEMBAKAU NON ROKOK: LANGKAH MAJU KABUPATEN BANDUNG - Trimo, Lucyana; Hidayat, Syarif (Jurnal Agro Industri Perkebunan, 2021)
The cigarette industry is no less important influence on the Indonesian economy, that is, it has contributed significantly to both labor and state income through excise. The existence of the FCTC (Framework Convention on Tobacco Control) causes the cigarette industry to experience very strong public pressure, especially in relation to the launching of the global agenda for World Health Day. To anticipate the impact of the FCTC, there needs to be technological innovation in a variety of processed non-cigarette tobacco products. The research method used was a survey with a descriptive quantitative approach. Respondents (tobacco farmers) were taken in five districts in Bandung Regency, which have great potential for tobacco commodities, and are one of the centers of tobacco production after Garut regency in West Java. The five research areas are the target areas of the Department of Industry and Trade of Bandung Regency in developing non-cigarette tobacco products. Interviews were also conducted with informants, namely: the chairperson and management of the Tobacco Farmers Group, the Indonesian Tobacco Association, staff of relevant agencies (Disperindag), and community leaders in the study area. The FGD technique was also carried out. Research data is tabulated, described and analyzed through systems thinking approaches. The results showed that there were still many obstacles in developing agroindustry of non-cigarette tobacco products, and the development model had to be built in an integrated and comprehensive manner, because it was related to various stakeholders.